2D Black Phosphorus–Based Biomedical Applications. (4th February 2019) - Luo, Miaomiao; Fan, Taojian; Zhou, Yun; Zhang, Han; Mei, Lin
Abstract: Black phosphorus (BP) has increasingly attracted scientific attention since its first applications in biomedicine due to its unique properties and excellent biocompatibility. In particular, its layer‐dependent bandgap, moderate carrier mobility, large surface‐area‐to‐volume ratio, biodegradability, intrinsic photoacoustic properties, and biocompatibility make it an ideal candidate for use in photothermal therapy, photodynamic therapy, drug delivery, 3D printing, bioimaging, biosensing, and theranostics, which are reviewed here. In addition, the article discusses strategies to overcome challenges related to surface instability due to chemical degradation, a major obstacle for its application. This review not only provides a comprehensive summary on BP preparation and biomedical applications but also summarizes recent research and future possibilities. Abstract : 2D black phosphorus is extensively used in biomedicine due to its excellent physical and chemical properties. This review focuses on the current progress and future perspectives of 2D black phosphorus–based biomedical applications, including cancer therapy, diagnosis, and theranostics. In addition, the article discusses strategies to overcome challenges related to surface instability, a major obstacle for its application.